Suriname : agricultural investment alternatives to oil palm - IICA (IICA San JoseCR, 1992)
Identifies potential crops and livestock alternatives to replace oil palm on the oldest state-owned plantation in Suriname - Victoria, which has been devastated by a disease called spear rot.